Electrochemical Biosensor for Organophosphate Pesticides and Huperzine‐A Detection Based on Pd Wormlike Nanochains/Graphitic Carbon Nitride Nanocomposites and Acetylcholinesterase. Issue 2 (23rd July 2015) - Wang, Bingxin; Ye, Cui; Zhong, Xia; Chai, Yaqin; Chen, Shihong; Yuan, Ruo
Abstract: A new electrochemical biosensor was developed for organophosphorus pesticides (OPs) and huperzine‐A (hupA) detection based on Pd wormlike nanochains/graphitic carbon nitride (Pd WLNCs/g‐C3 N4 ) nanocomposites and acetylcholinesterase (AChE). The morphologies and components of the nanocomposites were analyzed by transmission electron microscopy (TEM) and X‐ray photoelectron spectroscopy (XPS). The Pd WLNCs/g‐C3 N4 nanocomposites could effectively immobilize enzymes and promote the signal amplification. Under the optimum condition, the proposed biosensor displayed well performance. The linear response ranges for the determination of OPs and hupA were 1.00 nM to 14.96 µM and 3.89 nM to 20.80 µM, respectively. The corresponding detection limits were 0.33 nM and 1.30 nM (S/N=3). Meanwhile, the biosensor owned good reproducibility and stability, and could also be applied to analyze practical samples, which would be a new hopeful method for pesticide analysis. Abstract :